Industrial districts and economic income: the income district effect - Vila Garrido, Jordi (Papeles de Europa, 2019)
This paper presents a first approximation to the district effect from the variable of economic rent, which has been called as a district - income effect. This approach to the district phenomenon is carried out from the Neomarshallian local development perspective in order to emphasize the centrality of the industrial district as a source of its own interpretations of economic change and its active subject. At an empirical level, an approximation is made to the contraction of the existence or not of the district - income effect in the Spanish industrial districts for the year 2013; These data are analyzed through the comparison of total income, per capita and per worker expressed by the industrial districts in relation to the rest of the typologies of local productive systems.
Keywords: District effect; industrial districts; local labour systems; small and medium enterprises